Peningkatan Kompetensi Guru Sekolah Dasar di Kota Makassar Dalam Mengembangkan Pembelajaran Berbasis Platform Digital - Haerana Haerana; Burhanuddin Burhanuddin; Abdi Abdi; Rosmiati Rosmiati (STKIP Andi Matappa, 2021)
The purpose of this service is to improve the knowledge and skills of teachers in developing learning through the use of digital platforms. The implementation method is the introduction of a number of digital learning platforms; Training on designing powerpoint-based learning videos; School website management training. From the results of the evaluation of these activities, it is known that 100% of participants have understood various digital platforms for learning, there are 96 % of participants have understood the procedures for making powerpoint-based learning videos and there are 100 % of participants have understood the mechanism for using school websites as learning media.